HUBUNGAN ANTARA MOTIVASI BERPRESTASI DAN BUDAYA ORGANISASI DENGAN KINERJA GURU SMP NEGERI - Mahyunir Mahyunir Mahyunir (UNIVERSITAS BENGKULU, 2016)
The objective of this research is to find out whether a positive correlation between the public vocational school teachers’ working motivation the school principal leadership and theirworking discipline. The sample of this Research are 65 teachers coming from 185 public vocational school teachers as population of the study. Correlation descriptive research method wasapplied in this study. The result of this research shows that (1) there was a positive correlation between the public teachers’ working motivation (X1) and their working discipline (Y); (2) their was a positive correlation between the public teachers’ perception toward the school principal leadership (X2) and their working discipline (Y); and (3) there was a positive correlation between the public teachers’ working motivation and perception toward the school principal leadership (X-1,2) and their working discipline (Y).Keywords: motivation, culture, teacher